The importance of communication in the development of higher education institutions in Angola - Kimbanda, Francisco Jachuca (2020)
It addresses the possible relevance of the documentary genre in the teaching-learning process of science, based on the concepts of pedagogy, didactics and communication. Attention is also paid to the state of the art in this regard and in the context of the Republic of Angola and its provinces. We look at the Escola Superior Politécnica de Malanje (ESPM), as an institution attentive to the demands of the new times and adaptation to the Angolan reality, and to its multiple problems, but also opportunities, without losing sight of its ends and, still, the observance of international canons, without a perspective of pioneering scientific research, as one of the three pillars of Higher Education Institutions (HEIs).